Rancang Bangun Coffee Roaster Machine Kapasitas 1 Kg dengan Menggunakan Pengatur Suhu dan Waktu Termostat Rex-C 100 - Dian Prabowo; Unggul Satria Jati; Windra Jaya (Politeknik Negeri Cilacap, 2020)
Coffee Roaster Machine with Temperature Controller and Timer Capacity 1 Kg is designed to optimize heat from the heater and has a cheaper price than the machines on the market. The goal in the design of Coffee Roasting Machine with Temperature and Timer is to design, manufacture, perform function tests and test the results of the machine. In the manufacture of this machine the author uses the design method approach of James H. Earle, image software using Solidworks 2017 and working drawings using ISO standards. From the methods that the authors do, obtained the results of the evaluation of the concept of draft decisions are Source pemerers using a DC electric motor with a 12 volt voltage, heat source using a heater with 1500 watts of power, and the total cost used to make this machine of Rp. 4.296.912,32.